THE STYLISTIC ANALYSIS OF LITERARY TRANSLATION FROM UZBEK INTO ENGLISH - Muladjonov, Shuxrat (Мир исследований, 2021)
This paper is devoted to stylistic analysis of literary translation from Uzbek into English by the examples of expressive means and stylistic devices. The peculiarities of Uzbek literary texts in its origin language, the author’s style and expressions, linguistic and stylistic approaches of the text include the transmission to target language, the ways and methods that can determine those peculiarities in English language. The identification of proper equivalency to source text stylistic devices and expressive means, the methods of preserving semantic meaning of source text stylistic devices into target text according to linguistic, extra-linguistic and socio-cultural approaches. The translator’s attitude towards the original source literary text and the translation to target language. The preservation of the semantic meaning of the source text into target text according to the equivalents norms and correspondences which has been chosen by the skills of translators. Levels as equivalent, sub-equivalent and non-equivalent or descriptive in a role of conveying the stylistic devices and expressive means into target language.